Polyamine cross-linked network structure with high stability as well as preparation method and application of polyamine cross-linked network structure

By designing the polyamine crosslinking network structure, the problem of inconsistent performance of existing CO2 solid amine adsorbents is solved, the high stability and excellent comprehensive performance of the adsorbent are achieved, the energy consumption of the capture process is reduced, and the industrial application is provided. potential.

CN119425625APending Publication Date: 2025-02-14NANJING TECH UNIV
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202310964135.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-02
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing CO2 solid amine adsorbents have problems with inconsistent performance, including poor circulation, insufficient water resistance and oxidation resistance, which leads to high regeneration energy consumption in the capture process, limiting their industrial applications.

Method used

The design process of polyamine crosslinking network structure is adopted to form a stable polyamine crosslinking network structure through the chemical reaction of the inorganic porous carrier with the coupling agent and the crosslinking agent, thereby improving the stability and performance of the adsorbent.

Benefits of technology

The high stability, excellent circulation, water resistance and oxidation resistance of the adsorbent are achieved, and the total energy consumption of the capture process is reduced, and the potential for industrial application is to be achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425625A_ABST
    Figure CN119425625A_ABST
Patent Text Reader

Abstract

The invention discloses a polyamine cross-linked network structure with high stability and a preparation method and application thereof, the structure takes an inorganic porous material as a carrier, the inorganic porous carrier and polyamine are cross-linked by using a silane coupling agent, and a cross-linking agent is introduced to cross-link polyamine molecules so as to form a solid adsorbent. The adsorbent still has more than 95% of adsorption capacity after 50 times of adsorption cycles, the desorption enthalpy is in the range of 50-80 kJ / mol, the regeneration energy consumption is in the range of 1.5-2.0 GJ / ton-CO2, and the high-stability and low-energy-consumption CO2 trapping characteristic enables the adsorbent to have large-scale application potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of environment, and specifically relates to the design and adjustment of a polyamine cross-linked network structure, and application thereof. Background Art

[0002] The "greenhouse effect" has become a global environmental problem. The CO2 in the atmosphere mainly comes from humans burning large amounts of fossil fuels and destroying forest vegetation. Its concentration has risen from 277ppm in 1750 to 420ppm in 2021, causing global warming and other environmental problems. Therefore, CO2 capture and storage technology is recognized as the main method to reduce CO2 emissions and address environmental problems. Currently, there are mainly solvent absorption method, membrane separation method, solid adsorption method, deep cold diversion method, etc. Among the many CO2 capture technologies, the alcohol amine solution absorption method has been commercially applied for more than 50 years, and aqueous solutions such as monoethanolamine and ethylenediamine are usually used as absorption liquids. However, this type of process has the disadvantages of strong corrosiveness, low thermal stability, and high energy consumption.

[0003] In recent years, solid CO2 adsorbents have attracted extensive attention and research. Compared with aqueous alcohol amine solutions, solid CO2 adsorbents have the advantages of low energy consumption, low corrosion, and good recyclability. Solid adsorbent carriers include porous materials such as carbon, zeolite molecular sieves, organic metal frameworks, and silicon-based materials. Polyamines (polyethyleneimine, triethylenetetramine, tetraethylenepentamine, etc.) are usually loaded on porous materials (100-2000m 2 / g) surface, thereby "opening up" the organic amine. On the one hand, more amine active sites are exposed for CO2 capture; on the other hand, it is beneficial to accelerate the diffusion rate of CO2, thereby accelerating the absorption rate.

[0004] There are usually two methods to load amines on the surface of porous materials. One is the direct impregnation method, in which the porous material is immersed in an organic amine solution, and the solvent is removed by rotary evaporation and other methods to achieve the purpose of loading. Although the preparation process of the impregnation method is simple, due to the lack of chemical bond interaction between the organic amine and the carrier, its cyclicity is poor (more than 50% of the adsorption capacity is lost in 5 to 20 cycles), especially water resistance, the organic amine is easy to fall off, and the adsorption enthalpy is relatively high (100 to 150 kJ / mol). Another method is the chemical grafting method, in which the organic amine and the carrier are connected by chemical bonds to achieve a more stable effect. The stability of the adsorbent can be improved to a certain extent, but its adsorption capacity is usually small (1 to 2 mmol / g). Patent CN104258828 discloses a large adsorption capacity CO2 adsorbent with a maximum adsorption capacity of 4.9 mmol / g. CN102527326 discloses a method of using kaolin group to prepare silicon oxide as an organic amine carrier to reduce the cost of material preparation. CN106552609 discloses a hierarchical porous silicon oxide block as a CO2 adsorbent, and its adsorption capacity is still above 95% after 8 cycles. The comprehensive properties of CO2 solid amine adsorbent, such as adsorption capacity, carrier, cyclicity, water resistance, oxidation resistance, and decomposition enthalpy, are crucial. It is necessary for various properties to work together to reduce the regeneration energy consumption of the capture process to 2GJ / ton-CO2, so that the industrial application of solid amine adsorbent can be realized. Summary of the invention

[0005] The purpose of the present invention is to solve the problem of incoordination of various properties of existing CO2 solid amine adsorbents and provide a design process for an easily controllable polyamine cross-linked network structure. The CO2 adsorbent prepared by the present invention has the characteristics of controllable network structure, simple and easy-to-control synthesis conditions, no corrosion, green and pollution-free, low cost, and excellent comprehensive performance.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] A method for preparing a polyamine cross-linked network structure with high stability, characterized in that the material is prepared by the following preparation method:

[0008] (1) First, the inorganic porous carrier powder is dispersed in solvent a, and a coupling agent and water are added and stirred for 1.5 to 2.5 hours to obtain a suspension A;

[0009] (2) dissolving the polyamine in solvent b, adding a crosslinking agent to react with the polyamine to obtain a suspension B;

[0010] (3) The suspension A and the suspension B are mixed, and the temperature is controlled within the range of 50-500° C. to perform vacuum rotary evaporation for 1.5 to 2.5 hours to obtain white solid particles; finally, the white solid particles are dried and solidified in an oven for 1.5 to 2.5 hours to obtain a CO2 adsorbent.

[0011] In the technical solution of the present invention, the coupling agent is 3-aminopropyltrimethoxysilane (CAS: 13822-56-5), 3-aminopropyltriethoxysilane (CAS: 919-30-2), γ-(2,3-epoxypropoxy)propyltrimethoxysilane (CAS: 65799-47-5), γ-glycidyloxypropyltriethoxysilane (CAS: 2602-34-8), 3-(2,3-epoxypropoxy)propyltrimethoxysilane (CAS: 919-30-2), One or more of methyl diethoxysilane (CAS: 2897-60-1), 3-(2,3-epoxypropoxy)propyl triethoxysilane (CAS: 3388-04-3), 3-(2,3-epoxypropoxy)propyl methyl dimethoxysilane (CAS: 65799-47-5), epoxy modified polysiloxane, epoxy silane oligomer, (3-chloropropyl) trimethoxysilane (CAS: 2530-87-2);

[0012] The inorganic porous carrier is one or more of silicon dioxide (CAS: 14808-60-7), white carbon black (14464-46-1), titanium oxide (CAS: 12065-65-5), aluminum oxide (CAS: 1344-2-1), magnesium oxide (CAS: 1309-48-4), and zirconium oxide (CAS: 1314-23-4), and its specific surface area is greater than or equal to 50m 2 / g.

[0013] In the technical solution of the present invention: the mass of the coupling agent is 0.01 to 3 times the mass of the inorganic porous carrier; preferably: the mass of the coupling agent is 0.01 to 1 times the mass of the inorganic porous carrier. The inventors found that when the mass of the coupling agent is lower than 0.01 times the mass of the inorganic porous carrier, the water resistance of the adsorbent will decrease; when the mass of the coupling agent is higher than 3 times the mass of the inorganic porous carrier, the adsorption amount of the adsorbent will decrease.

[0014] In the technical solution of the present invention, the cross-linking agent is one or more of maleic anhydride (CAS: 108-31-6), azelaic acid chloride (CAS: 123-98-8), malonic acid (CAS: 141-82-2), succinic acid (CAS: 110-15-6), glutaric acid (CAS: 110-94-1), adipic acid (CAS: 124-04-9), pimelic acid (CAS: 111-16-0), suberic acid (CAS: 505-45-6), azelaic acid (CAS: 123-99-9), and sebacic acid (CAS: 111-20-6);

[0015] The polyamine is one or more of polyethyleneimine (CAS: 9002-98-6) with a molecular weight of 600, 800, 1200, 1800, or 10000, polyphthalamide, tetraethylenepentamine (CAS: 112-57-2), polyimide (CAS: 62929-02-6), polyacrylic acid (CAS: 9003-01-4), polypropylene glycol (CAS: 25322-69-4), polyglycolide (CAS: 26124-68-5), pentaethylenehexamine (CAS: 4067-16-7), etc.

[0016] In the technical solution of the present invention, the mass of the cross-linking agent is 0.1 to 0.9 times the mass of the polyamine; the mass of the cross-linking agent is 0.1 to 0.5 times the mass of the polyamine. The inventors found that when the mass of the cross-linking agent is less than 0.01 times the mass of the polyamine, the polyamine cannot be effectively "stretched", and on the one hand, the absorption rate decreases, and on the other hand, the decomposition enthalpy increases; when the mass of the cross-linking agent is higher than 0.9 times the mass of the polyamine, the cross-linking agent will occupy too many amine sites, resulting in a decrease in the adsorption amount of the adsorbent.

[0017] In the technical solution of the present invention, the mass of the inorganic porous carrier is 0.1 to 50 times the mass of the polyamine; preferably, the mass of the inorganic porous carrier is 0.1 to 1 times the mass of the polyamine.

[0018] In the technical solution of the present invention, the solvent a and the solvent b are independently selected from one or more of methanol, ethanol, N,N-dimethylformamide and dichloromethane.

[0019] A polyamine cross-linked network structure with high stability is prepared by the method.

[0020] In the technical solution of the present invention, the polyamine cross-linked network structure prepared by the method is used as a CO2 adsorbent.

[0021] The adsorbent prepared by the present invention has excellent performance in various aspects such as adsorption capacity, water resistance, oxidation resistance, cyclability, and decomposition enthalpy. The total energy consumption of the capture process is lower than 2GJ / ton-CO2, and has the potential for industrialization.

[0022] The inorganic porous carrier-coupling agent solution prepared in the present invention aims to react with the hydroxyl groups on the surface of the inorganic porous carrier by hydrolysis of the coupling agent. The polyamine-crosslinking agent solution prepared aims to react with the amine groups on the crosslinking agent and the polyamine to produce a dehydration reaction, thereby crosslinking the polyamine molecules and making the entire polyamine molecular structure more stable. The prepared inorganic porous carrier-coupling agent solution and the polyamine-crosslinking agent solution are mixed and rotary evaporated, aiming to react the epoxy or carboxyl groups on the coupling agent with the amine groups on the polyamine, thereby crosslinking the crosslinked polyamine and the inorganic porous carrier through the coupling agent, so that it is not easy to fall off from the surface of the inorganic porous carrier.

[0023] The solvent described in the present invention is preferably methanol. On the one hand, the industrial price of methanol is lower than that of solvents such as ethanol and N,N-dimethylamide, which is beneficial to reducing costs; on the other hand, the boiling point of methanol is lower than that of solvents such as ethanol and N,N-dimethylamide, which is beneficial to reducing the energy consumption of the rotary evaporation process.

[0024] The present invention also provides performance tests such as the cyclicity, oxidation resistance, water resistance, and regeneration energy consumption of the polyamine cross-linked network structure prepared by the above process. At the same time, the present invention can flexibly control the polyamine cross-linked network structure, the preparation process is non-corrosive, green, low-cost, the preparation conditions and process are simple and easy to control, and it is conducive to large-scale production. The advantages and beneficial effects of the present invention are:

[0025] 1) The process described in the present invention can flexibly adjust the polyamine cross-linked network structure, so that CO2 can diffuse, adsorb and desorb faster in the network structure during the adsorption process.

[0026] 2) The advantage of the present invention is that it can carry out targeted network structure design for different CO2 gas sources, such as flue gas (14wt% CO2), biomethane (35wt% CO2), direct air capture (0.04wt% CO2), etc.

[0027] 3) Through the adjustment of the network structure, the prepared adsorbent has excellent comprehensive properties such as cyclability, antioxidant properties, water resistance, and regeneration energy consumption, and is suitable for large-scale expansion and industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 These are performance test diagrams of Examples 1-2 and Comparative Examples 1 and 11. DETAILED DESCRIPTION

[0029] The present invention is further described below in conjunction with specific embodiments. The following examples are only used to illustrate the present invention, but not to limit the present invention. The reagents used in the following Table 1 examples are conventional reagents available in the art unless otherwise specified; the methods used are conventional methods in the art unless otherwise specified.

[0030] Embodiment 1:

[0031] Weigh 50g of alumina, whose specific surface area is 50m 2 / g, 25g 3-aminopropyltriethoxysilane and 25g water are dispersed in 500g methanol and stirred for 2h using a stirring paddle to generate an aluminum oxide-3-aminopropyltriethoxysilane solution;

[0032] In addition, 20 g of polyethyleneimine with a molecular weight of 1800 and 4 g of azelaic acid chloride were weighed and dissolved in 100 g of methanol and stirred with a stirring paddle for 2 h to generate a polyethyleneimine-zelaic acid chloride solution.

[0033] The aluminum oxide-3-aminopropyltriethoxysilane solution and the polyethyleneimine-azelaoyl chloride solution were mixed and the vacuum degree was controlled. The methanol was completely removed by rotary evaporation for 2 h at 50° C. The obtained dry solid was cured in an oven at 105° C. for 2 h to obtain a sample.

[0034] Embodiment 2:

[0035] Weigh 50g of silicon oxide, whose specific surface area is 150m 2 / g, 25g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and 25g of water are dispersed in 500g of methanol and stirred for 2h using a stirring paddle to generate a silicon oxide-γ-(2,3-epoxypropoxy)propyltrimethoxysilane solution;

[0036] In addition, 20 g of polyethyleneimine with a molecular weight of 1800 and 4 g of maleic anhydride were weighed and dissolved in 200 g of methanol and stirred with a stirring paddle for 2 hours to generate a polyethyleneimine-maleic anhydride solution. The silicon oxide-γ-(2,3-epoxypropoxy)propyltrimethoxysilane solution and the polyethyleneimine-maleic anhydride solution were mixed and the vacuum degree was controlled. At 100°C, the methanol was completely removed by rotary evaporation for 2 hours. The obtained dry solid was cured in an oven at 105°C for 2 hours to obtain a sample.

[0037] Embodiment 3:

[0038] Weigh 50g of silicon oxide, whose specific surface area is 300m 2 / g, 25g of γ-glycidyloxypropyltriethoxysilane and 25g of water are dispersed in 500g of methanol and stirred with a stirring paddle for 2.5h to generate a silicon oxide-γ-glycidyloxypropyltriethoxysilane solution;

[0039] In addition, 20 g of polyethyleneimine with a molecular weight of 1800 and 4 g of azelaic acid were weighed and dissolved in 100 g of methanol and stirred with a stirring paddle for 2 hours to generate a polyethyleneimine-zelaic acid solution. The silicon oxide-γ-glycidyloxypropyltriethoxysilane solution and the polyethyleneimine-zelaic acid solution were mixed and the vacuum degree was controlled. At 50-200°C, the methanol was completely removed by rotary evaporation for 2 hours. The obtained dry solid was cured in an oven at 105°C for 2 hours to obtain a sample.

[0040] Embodiment 4:

[0041] Weigh 50g of silicon oxide, whose specific surface area is 400m 2 / g, 25g of 3-(2,3-epoxypropoxy)propylmethyldiethoxysilane and 25g of water are dispersed in 500g of methanol and stirred with a stirring paddle for 2.5h to generate a silicon oxide-3-(2,3-epoxypropoxy)propylmethyldiethoxysilane solution;

[0042] In addition, 20 g of polyethyleneimine with a molecular weight of 1800 and 4 g of adipic acid were weighed and dissolved in 100 g of methanol and stirred with a stirring paddle for 2 hours to generate a polyethyleneimine-adipic acid solution. The silicon oxide-3-(2,3-epoxypropoxy)propylmethyldiethoxysilane solution and the polyethyleneimine-adipic acid solution were mixed and the vacuum degree was controlled. At 50-200°C, the methanol was completely removed by rotary evaporation for 2 hours. The obtained dry solid was cured in an oven at 105°C for 2 hours to obtain a sample.

[0043] Embodiment 5:

[0044] Weigh 50g of the silica-alumina composite carrier (including 20g of silica and 30g of alumina), with a specific surface area of ​​500m 2 / g, 25g 3-(2,3-epoxypropoxy)propyltriethoxysilane and 25g water were dispersed in 500g methanol and stirred with a stirring paddle for 2.5h to generate a silica-alumina composite carrier-3-(2,3-epoxypropoxy)propyltriethoxysilane solution;

[0045] In addition, 20 g of polyethyleneimine with a molecular weight of 1800 and 4 g of suberic acid were weighed and dissolved in 100 g of methanol and stirred with a stirring paddle for 2 h to generate a polyethyleneimine-suberic acid solution.

[0046] The silica-alumina composite carrier-3-(2,3-epoxypropoxy)propyltriethoxysilane solution and the polyethyleneimine-suberic acid solution were mixed and the vacuum degree was controlled. The methanol was completely removed by rotary evaporation for 2 hours at 50-200° C. The obtained dry solid was cured in an oven at 105° C. for 2 hours to obtain a sample.

[0047] Comparative Example 1:

[0048] Other conditions were the same as in Example 1, except that the amount of polyethyleneimine was 3000 g.

[0049] Comparative Example 2:

[0050] Other conditions were the same as in Example 1, except that the amount of polyethyleneimine was 1 g.

[0051] Comparative Example 3:

[0052] Other conditions were the same as in Example 1, except that the amount of azelayl chloride was 0.1 g.

[0053] Comparative Example 4:

[0054] Other conditions were the same as in Example 1, except that the amount of azelayl chloride was 100 g.

[0055] Comparative Example 5:

[0056] Other conditions were the same as in Example 2, except that the stirring was carried out with a stirring paddle for 1 h.

[0057] Comparative Example 6:

[0058] Other conditions were the same as in Example 2, except that the stirring was carried out with a stirring paddle for 3 h.

[0059] Comparative Example 7:

[0060] Other conditions were the same as in Example 3, except that the rotary evaporation was carried out for 1 h.

[0061] Comparative Example 8:

[0062] Other conditions were the same as in Example 3, except that the rotary evaporation was carried out for 3 h.

[0063] Comparative Example 9:

[0064] Other conditions were the same as in Example 3, except that the curing was performed for 1 h.

[0065] Comparative Example 10:

[0066] Other conditions were the same as in Example 3, except that the curing was performed for 3 h.

[0067] Comparative Example 11:

[0068] Other conditions were the same as in Example 3, except that the molecular weight of polyethyleneimine was 18,000.

[0069] The CO2 adsorption performance of the above examples and comparative examples was tested, and three CO2 adsorption scenarios were simulated using a thermogravimetric analyzer, namely 14% CO2 (flue gas) and 35% CO2 (biogas), as well as direct air capture. The water resistance of different samples was measured (the samples were immersed in water for 10 minutes, and the adsorption amount was measured after drying), and the oxidation resistance (the samples were placed in an oven at 120°C for 24 hours, and then the adsorption amount was measured). The cyclicity was tested by a fixed bed under oxygen-free and water-free conditions. The analytical enthalpy was measured by a scanning calorimeter as well as the regeneration energy consumption.

[0070] The test results of the three CO2 adsorption scenarios are shown in Tables 2, 3, and 4, respectively. It can be seen that under the conditions of 14% and 35% CO2, the adsorption capacity of the adsorbent prepared in the embodiment is generally around 2.5mmol / g, while for air capture, the adsorption capacity is around 1.2mmol / g (the adsorption capacity of the comparative example is significantly lower than that of the embodiment). And with the increase of the adsorption temperature, the adsorption capacity shows a trend of first increasing and then decreasing. This is because the increase in temperature strengthens the material transfer process in the adsorption process, thereby increasing the adsorption capacity; and with the further increase in temperature, the adsorption process and desorption process of the adsorbent show a situation of mutual game, the desorption rate is greater than the adsorption rate, and thus the adsorption capacity decreases. The water resistance and oxidation resistance of the adsorbent are both above 90%. It is worth noting that the decomposition enthalpy of the adsorbent is between 50 and 80kJ / mol, and the energy consumption is between 1.5 and 2.5GJ / tonCO2. Taking into account the adsorption capacity, water resistance, oxidation resistance and regeneration energy consumption of the adsorbent, and conducting cyclic stability tests on some samples, such as the attached Figure 1 As shown, it can be seen that after 50 cycles of adsorption and desorption, Example 2 still has an adsorption amount of more than 95%, while the adsorption amount of Comparative Example 1 has dropped to about 75%. Therefore, the adsorbent prepared in this article has the potential for industrial application.

[0071] Table 2 Comparison of various performances of different examples (14% CO2)

[0072]

[0073]

[0074] Table 3 Comparison of various performances of different examples (35% CO2)

[0075]

[0076]

[0077] Table 4 Comparison of performance of different examples (air capture)

[0078]

Claims

1. A method for preparing a polyamine cross-linked network structure with high stability, characterized in that: The material is prepared by the following preparation method: (1) First, the inorganic porous carrier powder is dispersed in solvent a, and a coupling agent and water are added and stirred for 1.5 to 2.5 hours to obtain a suspension A; (2) dissolving the polyamine in solvent b, adding a crosslinking agent to react with the polyamine to obtain a suspension B; (3) The suspension A and the suspension B are mixed, and the temperature is controlled within the range of 50-500° C. to perform vacuum rotary evaporation for 1.5 to 2.5 hours to obtain white solid particles; finally, the white solid particles are dried and solidified in an oven for 1.5 to 2.5 hours to obtain a CO2 adsorbent.

2. The preparation method according to claim 1, characterized in that: The coupling agent is one or more of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-glycidyloxypropyltriethoxysilane, 3-(2,3-epoxypropoxy)propylmethyldiethoxysilane, 3-(2,3-epoxypropoxy)propyltriethoxysilane, 3-(2,3-epoxypropoxy)propylmethyldimethoxysilane, epoxy-modified polysiloxane, epoxysilane oligomer, and (3-chloropropyl)trimethoxysilane; The inorganic porous carrier is one or more of silicon dioxide, white carbon black, titanium oxide, aluminum oxide, magnesium oxide, and zirconium oxide, and its specific surface area is greater than or equal to 50m 2 / g.

3. The preparation method according to claim 2, characterized in that: The mass of the coupling agent is 0.01 to 3 times the mass of the inorganic porous carrier; preferably, the mass of the coupling agent is 0.01 to 1 times the mass of the inorganic porous carrier.

4. The preparation method according to claim 1, characterized in that: The cross-linking agent is one or more of maleic anhydride, azelaic acid chloride, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, and sebacic acid; The polyamine is one or more of polyethyleneimine, polyphthalamide, tetraethylenepentamine, polyimide, polyacrylic acid, polypropylene glycol, polyglycolide, pentaethylenehexamine, etc., with a molecular weight of 600, 800, 1200, 1800 or 10000.

5. The preparation method according to claim 4, characterized in that: The mass of the cross-linking agent is 0.1 to 0.9 times the mass of the polyamine; the mass of the cross-linking agent is 0.1 to 0.5 times the mass of the polyamine.

6. The preparation method according to claim 1, characterized in that: The mass of the inorganic porous carrier is 0.1 to 50 times the mass of the polyamine; preferably, the mass of the inorganic porous carrier is 0.1 to 1 times the mass of the polyamine.

7. The preparation method according to claim 1, characterized in that: The solvent a and solvent b are independently selected from one or more of methanol, ethanol, N,N-dimethylformamide and dichloromethane.

8. A polyamine cross-linked network structure with high stability, characterized in that: The polyamine cross-linked network structure is prepared by the method described in any one of claims 1 to 7.

9. Use of the polyamine cross-linked network structure obtained by the method of claim 1 as a CO2 adsorbent.

Citation Information

Cited By

  • CO2 adsorbent as well as preparation method and application thereof

    CN121467003A

  • Solid amine adsorbent, preparation method thereof and CO2 trapping process

    CN121490737A

  • Solid waste source solid amine adsorbent and preparation method thereof

    CN121847073A